Ultrasonic Studies on Certain Surfactants - KOTHAI, S. (Asian Journal of Chemistry, 2010)
Ultrasonic velocities (u) and densities (ρ) have been measured for the aqueous solutions of three surfactants in presence of chloramine-T at various concentrations and at 303 K. Acoustical parameters such as adiabatic compressibility (κ), free length (Lf), surface tension (γ), molar surface energy (E) and surface area (Y) are evaluated. The trend in the acoustical parameters and the surface properties of surfactants with various concentrations of detergents suggest the aggregation of surfactant molecules at critical micellar concentration. The trend in the influence of chloramine-T on detergent action on the three surfactants at 303 K in aqueous solutions are investigated.